(untitled) (Proceedings of Southern Federal University. Philology, 2024)
DOI 10.18522/1995-0640-2024-4-128-140 The key option to this piece of art of early writings is the idea of the person’s fate, conceived in the light of people-versed prejudices. The people’s feeling by Sholokhov is determined in guessing the darken reasons of the things, mystic forebodings, sacralization of routine things and situations, fundamental estimation of must-have and possible thins, in a certain interpretation of existence. Taking into consideration all the mentioned above this article represents the analysis of the subjective-narrative strategy of the short novel, sense possibilities of a narrative as a folk basis (possible interchanges with the plots of the folk fairy tales). Coming-back and saying goodbye has been interpreted as the climax of epic situations in the short novel. Key words: M.A. Sholokhov, “The Don Stories”, “The Blood of the Stranger”, fate, folk narrative, tale, humanism, sacral, ritual, epic, tragic collision, retelling about existence